Penelitian Ini Berjudul Pengaruh Motivasi, Kemampuan Dan Komitmen Terhadap Kinerja Dosen Di Universitas Islam Malang - Salim, Ali Meeloud Ali; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research is entitled The Influence of Motivation, Ability and Commitment on Lecturer Performance at the Islamic University of Malang. The aim of this research is to find out whether there is or there is no influence of motivation, ability and commitment on the performance of lecturers at Malang Islamic University. The object of this research is questionnaire data, the analysis technique used in this research is parametric inferential statistics which is assisted using the SPSS application. The results of the inter-achievement analysis of this research show that the variables Motivation, Ability and Commitment have an influence on lecturer performance. Keywords : Motivation, Ability, Commitment